GROUPOID POWERS - Čupona, Ǵorǵi; Celakoski, Naum; Ilić, Snežana (Matematichki Bilten, 2001)
The following statement is the main result of the paper. If \(V\) is the variety of groupoids (commutative groupoids), or \(V\) is the variety of \(n\)-idempotent groupoids (commutative \(n\)-idempotent groupoids), i.e. groupoids (commutative groupoids) with an axiom \(x^n+1=x\), \(n≥ 2\), then the monoid of powers is free with a countable infinite basis.